Cortical alpha rhythms are correlated with body sway during quiet open-eyes standing in athletes: A high-resolution EEG study - Del Percio, C.; Brancucci, A.; Bergami, F.; Marzano, N.; Fiore, A.; Di Ciolo, E.; Aschieri, P.; Lino, A.; Vecchio, F.; Iacoboni, M. (Neuroimage, 2007)
Electroencephalographic (EEG; Be-plus Eb-Neuro©) and stabilogram (RGM©) data were simultaneously recorded in 19 elite karate and 18 fencing athletes and in 10 non-athletes during quiet upright standing at open- and closed-eyes condition in order to investigate the correlation between cortical activity and body sway when the visual inputs are available for balance. Our working hypothesis is that, at difference of non-athletes, athletes are characterized by enhanced cortical information processing as indexed by the amplitude reduction of EEG oscillations at alpha rhythms (about 8-12 Hz) during open- referenced to closed-eyes condition (event-related desynchronization, ERD). Balance during quiet standing was indexed by body "sway area". Correlation between alpha ERD and event-related change of the sway area was computed by a non-parametric test (p < 0.05). It was found that alpha ERD (10-12 Hz) is stronger in amplitude in the karate and fencing athletes than in the non-athletes at ventral centro-parietal electrodes of the right hemisphere (p < 0.02). Furthermore, there was a statistically significant correlation in the karate athletes between right ventral centro-parietal alpha ERD and body sway area (r = 0.61; p < 0.008): specifically, the greater the alpha ERD, the greater the percentage reduction of the body sway area when the visual inputs were available. These results suggest that parasylvian alpha ERD of the right hemisphere may reflect the cortical information processing for the balance in elite athletes subjected to a long training for equilibrium control.